Investor institusional dan keinformatifan laba di Indonesia dan Jepang - Rahmaniati , Ni Putu Gita; Ekawati, Erni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study examines the existence of institutional investors who can play a role in increasing earnings informativeness through income increasing-earnings management and income smoothing. The hypothesis was developed on the basis of the view that the motivation behind earnings management decisions is to increase the informativeness of earnings reports. The study employs sample of manufacturing companies listed on the Indonesia Stock Exchange and the Japan Stock Exchange for the period of 2010-2018. Ordinary least square and weighted least square regression models are used in cross-sectional statistical testing, which is carried out annually throughout the 2014-2018 observation period. In Japan, institutional ownership has a positive and significant effect on income increasing- earnings management, and on reverse income smoothing, as well, while these are not the case in Indonesia. This study reveals that in Japan, the institutional investors play a role of monitoring that can encourage managers to increase earnings informativeness through earnings management-income increasing followed by reverse income smoothing. This condition is not found in Indonesia. It is possible that in Indonesia, the institutional investors play a role of controlling, that may promote managerial opportunistic behavior.